A reduction in metabolism explains the tradeoffs associated with the long-term adaptation of phytoplankton to high CO2 concentrations - Jin, Peng (The New phytologist, 2022)
© 2021 The Authors. New Phytologist © 2021 New Phytologist Foundation.